ANALYSIS OF FACTORS INFLUENCING THE USAGE OF MYTELKOMSEL APPLICATION IN MAKASSAR - Hery Bagio Wahari; Sapta Asmal; Kifayah Amar (Center for Study and Journal Management FTI UMI, 2023)
This study aims to analyze factors influencing the usage of MyTelkomsel application based on Technology Acceptance Model (TAM) theory. Data are collected using offline questionnaires distributed to MyTelkomsel application users in Makassar region and its surrounding areas. Data analysis is performed using multiple linear regression after conducting tests for validity, reliability, and classical assumptions. The results of the F-test indicate that overall, all variables collectively influence the usage variable. The results of the partial t-test show that trust, habit, perceived usefulness, and attitude are proven to be influential factors in the usage of MyTelkomsel application, while perceived ease of use and subjective norm do not have a significant impact. This study obtains an adjusted R-Square of 0.577, indicating that the examined factors can explain approximately 57.7% of the variation in the usage of MyTelkomsel application.